Synoptikon : Streams of Tradition in Mark, Matthew, and Luke - Chilton, Bruce D. (The New Testament Gospels in their Judaic Contexts, 2022)
The Synoptikon presents the texts of the Synoptic Gospels alongside one another and in relation to their Judaic contexts. Discrete typefaces highlight particular streams of tradition that interacted so as to produce the Gospels. The depth of the Synoptic tradition consequently emerges, as well as its breadth.